Lipid-Lowering Effects of Lotus Leaf Alcoholic Extract on Serum, Hepatopancreas, and Muscle of Juvenile Grass Carp via Gene Expression - Yao, Junpeng; Hu, Pengcheng; Zhu, Yanhong; Xu, Yingyan; Tan, Qingsong; Liang, Xufang (Frontiers in Physiology, 2020)
Compared with wild grass carp (Ctenopharyngodon idellus), fish from intensive culture resulted in disordered lipid metabolism, showing excess lipid deposition in hepatopancreas and muscle. The leaf of lotus prevents fat accumulation in humans and may have similar effects on fish. This study explored the regulatory mechanisms by which the dietary addition of an alcoholic extract of lotus leaf (AELL) reduced lipid deposition in the hepatopancreas and muscle of juvenile grass carp. The fish (average initial weight: 34.00±0.40 g) were fed four experimental diets containing different AELL levels (0, 0.07, 0.14, and 0.21%) for 8 weeks. Serum components, lipid droplet size, triacylglycerol (TAG) content, enzymatic activities and mRNA levels of genes related to lipid metabolism in the hepatopancreas and muscle were analyzed. The results showed that dietary AELL supplementation significantly reduced the TAG content, lipid droplet area in the histological sections as well as the fatty acid synthase (FAS) activity in both the hepatopancreas and muscle, but enhanced the activities of lipoprotein lipase (LPL) and carnitine palmitoyltransferase I  (CPT1) in both tissues. In addition, dietary AELL supplementation decreased the mRNA expression of genes involved in fatty acid uptake (cd36, fatp1/fatp4/fatp6, fabp10/fabp11, acsl1/acsl4) and de novo lipid synthesis (pgd, g6pd and fasn) as well as the transcription factors pparg and srebf1 in the hepatopancreas and muscle, but increased the mRNA levels of genes relating to lipid catabolism (cpt1a, lipe, pnpla2, lpl), lipid transportation (apob), and the transcription factor ppara in both tissues. In conclusion, dietary AELL supplementation reduced the lipid accumulation in the hepatopancreas and muscle by affecting the gene expression of proteins with known effects on lipid metabolism in juvenile grass carp.